Finite element modelling of thermo-elastoplastic behaviour of hot-rolled steel profiles submitted to fire - Fonseca, E.M.M. (2010)
This paper presents finite element algorithms developed to simulate the thermoelastoplastic behaviour of steel profiles under high temperatures, in particular those arising from fire conditions. Transient analyses of the temperature field and the mechanical response at each instant have been done. The thermal response obtained with the finite element formulation and the results obtained using the simplified heat conduction equation according to the Eurocode 3 have been compared for several series of hot-rolled steel profiles. The nonlinearity of the problem due to the thermal dependence of the material properties has been taken into account and an elastoplastic model has been used.